PERAN PESANTREN DALAM MENINGKATKAN KETERAMPILAN BEKERJA SAMA DI PONDOK PESANTREN PUTRI UMI KULSUM ADNAN DIWEK JOMBANG - Gama Fesnari; Aida Arini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Pesantren is a local form of Islamic educational institution in Indonesia that plays an important role in character building and developing the skills of students. One of the skills that is a concern in life in pesantren is cooperation skills. Pesantren naturally provides a conducive environment for the development of cooperation skills in students through daily life and teaching Islamic values that emphasize cooperation and social concern. The focus of the research is (1) How are the cooperation skills of students at the Umi Kulsum Adnan Diwek Jombang Girls’ Islamic Boarding School. (2) What is the role of pesantren in improving the cooperation skills of students at the Umi Kulsum Adnan Diwek Jombang Girls’ Islamic Boarding School. The method used in this study is qualitative which is descriptive, with a case study approach and the data collection techniques used are observation, interviews, and documentation. The informants in this study consisted of the Boarding School Caretaker, Boarding School Administrators, and Students. The results of the study (1) The cooperative skills of students at the Umi Kulsum Adnan Diwek Jombang female Islamic boarding school are developed through various Islamic boarding school programs that involve cooperation. Challenges in cooperation faced by students include differences in background and character, such as students who are active and those who lack initiative, lack of communication and differences of opinion. However, through the habit of daily cooperation and guidance from the Islamic boarding school, students can develop a proactive attitude and be more ready to work in a team. (2) The role of Islamic boarding schools in improving cooperative skills is very significant. Islamic boarding schools as social institutions that provide an environment based on collective life and a dormitory system that acts as a facilitator and encourages students to interact intensively, so that they can form effective communication. The programs provided by Islamic boarding schools can also improve discipline, form a sense of responsibility, can train leadership and slowly students are able to adapt. The coaching program implemented by Islamic boarding schools contributes to forming good cooperation among students.